Changes in antennal gene expression underlying sensory system maturation in Rhodnius prolixus. (January 2022) - Latorre-Estivalis, Jose Manuel; Große-Wilde, Ewald; da Rocha Fernandes, Gabriel; Hansson, Bill S.; Lorenzo, Marcelo Gustavo
Abstract: Triatomine bugs are the blood feeding insect vectors transmitting Chagas disease to humans, a neglected tropical disease that affects over 8 million people, mainly in Latin America. The behavioral responses to host cues and bug signals in Rhodnius prolixus are state dependent, i.e., they vary as a function of post-ecdysis age. At the molecular level, these changes in behavior are probably due to a modulation of peripheral and central processes. In the present study, we report a significant modulation of the expression of a large set of sensory-related genes. Results were generated by means of antennal transcriptomes of 5 th instar larvae along the first week (days 0, 2, 4, 6 and 8) after ecdysis sequenced using the Illumina HiSeq platform. Significant age-induced changes in transcript abundance were established for more than 6120 genes (54, 7% of 11, 186 genes expressed) in the antenna of R. prolixus . This was especially true between the first two days after ecdysis when more than 2500 genes had their expression significantly altered. In contrast, expression profiles were almost identical between day 6 and 8, with only a few genes showing significant modulation of their expression. A total of 86 sensory receptors, odorant carriers and odorant degrading enzymes were significantly modulated across age points and clustered into three distinct expression profiles. The set of sensory genes whose expression increased with age (profile 3) may include candidates underlying the increased responsiveness to host cues shown by R. prolixus during the first days after molting. For the first time, we describe the maturation process undergone at the molecular level by the peripheral sensory system of a hemimetabolous insect. Graphical abstract: Image 1 Highlights: Triatomine responsiveness for host search depends on post-ecdysis age. Gene expression changes underlying this behavioral maturation are unknown. We generated 35 antennal transcriptomes at five larval age points. Most age-induced expression changes concentrated in the first 2 days post-ecdysis. Gene candidates underlying increased responsiveness to host cues are proposed.